Building Students' Discipline Through The Example Set By Primary School Teachers - Khotijah, Siti; Ramadhany, Farella; Amilia, Amrotul; Syuwairiyah, Witri; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the role of teacher exemplarity in building students’ discipline character at the elementary school level, particularly at SDN Ellak Laok IV, Sumenep Regency. The background of this research stems from the low level of students’ discipline and responsibility in fulfilling their school obligations, including punctuality, neatness, and adherence to school rules. Teacher exemplarity is considered a key factor in character formation, as teachers serve as role models whose behavior is imitated by students. This research employs a qualitative approach using library research methods, analyzing relevant literature and interview findings to gain a deeper understanding of the phenomenon. The results show that teacher exemplarity has a significant influence on the development of students’ discipline. Teachers at SDN Ellak Laok IV demonstrate discipline through punctuality, neat appearance, consistency in conducting learning activities, and fair implementation of reward and punishment systems. Furthermore, positive habits such as praying before class and maintaining politeness are effective means of instilling character values. Thus, teachers not only act as educators but also as moral role models who shape students’ personalities and behavior. This study highlights the importance of teacher exemplarity as a central strategy in fostering discipline and responsibility among elementary school students within the framework of character education